Pengaruh Pertumbuhan Ekonomi, Upah Minimum, Tingkat Pengangguran Terbuka Dan Pendidikan Terhadap Jumlah Penduduk Miskin - Hapsari Wiji Utami; Siti Umajah Masjkuri (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2018)
Introduction: This study examines the effects of economic growth, minimum wages, open unemployment and education (average length of school) on the number of poor people in districts / cities in East Java Province. The purpose of this research is expected to be able to analyze how and how much influence economic growth, minimum wages, open unemployment and education (average length of schooling) on the number of poor people in East Java, so that later it is expected to be used as one of the bases in determining policy in overcoming the problem of poverty in East Java. Methods: The data used in this study are secondary data obtained from the Central Statistics Agency (BPS) and the Manpower Office as supporters. The analysis method used in this research is panel data regression analysis method with the FEM method with the help of Eviews 6 software. Results: The results of this study indicate that the Economic Growth variable has a negative but insignificant effect on the level of the number of poor people, the Minimum Wage variable has a significant negative effect on the number of poor people, the Open Unemployment Rate variable has a significant negative effect on the number of poor people and the Education variable (long average schools have a significant negative effect on the number of poor people in East Java. Conclusion and suggestion: The provincial government of East Java should increase the total production of goods and services produced in all districts / cities in East Java, taking into account the provincial minimum wage so that it can reduce the number of poor people in all districts / cities in East Java and further stimulate the formal sector.